THE RELATIONSHIP BETWEEN ORGANIZATIONAL CLIMATE AND WORK MOTIVATION TO ORGANIZATIONAL COMMITMENT IN PT. CITRA ABADI ABADI - Berti Anggun Melati; Anoesyirwan Moeins; Martinus Tukiran (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The purpose of this study was to examine the strengths of the relationship between organizational climate and work motivation and commitment to organization in PT. True Eternal Image. The study population was the operator of PT. Citra Abadi Sejati as many as 454 operators with a sample size of 213 operators calculated using the Slovin formula with an error rate of 5%. Collecting data for each variable studied using a questionnaire with a rating scale. The data analysis technique used descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: (a) There is a significant positive relationship between Organizational Climate and Commitment to Organization with a correlation coefficient of ry.1 = 0.579, the strength of the relationship is